Les aqueducs romains de Lyon et d’ailleurs : nouveaux repères - Aldo Borlenghi; Catherine Coquidé (Gallia)
To introduce the topic of “Roman aqueducts and of Lyon and elsewhere: New points of reference” is to follow in the footsteps of several generations of researchers from the 16th century onwards, as well as to present the framework of contemporary archaeological research.The authors are not the first to follow this path. Over the past three decades, a vast amount of data has been collected, which had to be shared and organised. The “Aqueducts of Lyon” research group, which all the researchers, regardless of their institutional affiliations were invited to join, has been at work since 2015: professional archaeologists from government departments, universities, laboratories, institutes or companies, as well as research volunteers, have joined forces to present and explain their work within different institutional frameworks, and with different tools and methods. Ten meetings were organised, culminating in an international conference held in Lyon in October 2020. More than forty authors have contributed to this volume.Mostly unpublished material from Lyon and other Roman canals in France, Switzerland, Spain and Italy is brought together under four categories –routes, construction works, dating, water distribution in the city.The “routes” category covers the identification and protection of aqueduct remains everywhere in the countryside and the city. It emerges that this theme is closely bound to a number of sometimes interdependent research topics.“Construction works” draws contributions from new obervations at different scales: the design of a new section of aqueduct, the organisation of construction sites and the supply of materials, the building of a canal from the foundations upwards, the handling of factors that impact water flow. Advanced hydraulic engineering such as siphons and some dropshafts or hydraulic jumps are also covered.The “dating” category is the focus of multiple questions as it brings into play a first of politics, large-scale investment and urban amenities. Numerous clues can be used in chasing down a chronology, but uncertainty is often the rule and multiple pieces of evidence have to intersect in order to arrive at plausible conclusions.Finally, bringing water into the city centre is the ultimate purpose. Public infrastructures, Roman baths, fountains, residential areas, reservoirs or cisterns and collecting channels are among the common destinations of water flow. Much remains to be discovered in order to track water systems, to understand how they operate and how other water resources are exploited.Some topics, such as catchment areas, flow characterisation, dates of abandonment or the Roman legal framework of use and local regulation, so far remain beyond reach or unevenly documented.The aim of this book is to outline the current state of knowledge on one of the largest water networks of its time and to pave the way for future research.